THE CONTENT AND ESSENCE OF USING AL-HAKIM AL-TIRMIZI'S PEDAGOGICAL VIEWS IN THE HIGHER EDUCATION SYSTEM - Erdanova Zamira Olimovna (Scholar Express Journal, 2023)
This article highlights the problem of using Al-Hakim al-Tirmizi's pedagogical views in the higher education system, the pedagogical features of using AlHakim at-Tirmizi's pedagogical views in the higher education system, and the use of Al-Hakim at-Tirmizi's pedagogical views in the higher education system. written about the conditions.
Keywords: Pedagogy; higher education; education; system